Financial Resilience Amidst the Pandemic: A Study on Net Interest Margin and Key Banking Ratios in Indonesia - Fauziah, Ulfah Nurillahi; Nugroho, Lucky; Hidayah, Nurul (Economics & Islamic Finance Journal (ECIF), 2024)
This study aims to analyze the influence of credit disbursement ratio, low-cost fund ratio, efficiency ratio, and credit quality on Net Interest Margin (NIM) in the conventional banking industry in Indonesia before and during the COVID-19 pandemic. The formulation of the problems raised in this study includes how these financial ratios affect NIM in stable economic conditions and crises such as pandemics. The research method used is quantitative with a causal associative approach, using panel data from 46 conventional banks listed on the Indonesia Stock Exchange (IDX) during 2017-2022. The study results show that the credit disbursement ratio did not significantly affect NIM before the pandemic but had a significant influence during the pandemic. The ratio of low-cost funds did not significantly affect NIM before or during the pandemic. The efficiency ratio significantly affected NIM in both periods, demonstrating the importance of operational efficiency in maintaining bank profitability. Credit quality only significantly influenced NIM during the pandemic, where high credit risk impacted increasing interest rates to compensate for such risks. This research makes a theoretical contribution by enriching the literature on banking risk management in crises. In practical terms, these findings reference bank management's strategic decisions to maintain financial stability amid severe economic challenges. The latest of this research lies in comparative analysis before and during the pandemic, which provides insight into financial dynamics amid a crisis.